2021
DOI: 10.3800/pbr.16.100
|View full text |Cite
|
Sign up to set email alerts
|

Use of environmental DNA to survey the distribution of the invasive mussel <i>Limnoperna fortunei</i> in farm ponds

Abstract: The golden mussel Limnoperna fortunei (Dunker, 1857) is an invasive freshwater bivalve species that exerts harmful effects on the environment, as well as man-made structures, such as water-treatment systems. By using conventional sampling methods, it is difficult to detect mussels under low-density conditions; however, environmental DNA (eDNA) analysis may be a rapid and efficient method for monitoring this aquatic organism. In this study, we conducted surveys based on the eDNA analysis of L. fortunei in 15 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…On the other hand, only 17% of the studies were performed both in the field and also under controlled environments (i.e. mesocosms, aquariums, lab tanks, and artificial ponds, among others) (Dejean et al, 2011;Ito and Shibaike, 2021;Ladell et al, 2019;Matejusova et al, 2021;Mauvisseau et al, 2018;Mizumoto et al, 2018;Takeuchi et al, 2019;Troth et al, 2020;Turner et al, 2015;Yoshitake et al, 2019), and an even lower percentage was conducted exclusively under controlled conditions (8.7%) Mizumoto et al, 2018;Seymour et al, 2018;Stoeckle et al, 2017) (Fig. 8, Table S2).…”
Section: Environmental Factors Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, only 17% of the studies were performed both in the field and also under controlled environments (i.e. mesocosms, aquariums, lab tanks, and artificial ponds, among others) (Dejean et al, 2011;Ito and Shibaike, 2021;Ladell et al, 2019;Matejusova et al, 2021;Mauvisseau et al, 2018;Mizumoto et al, 2018;Takeuchi et al, 2019;Troth et al, 2020;Turner et al, 2015;Yoshitake et al, 2019), and an even lower percentage was conducted exclusively under controlled conditions (8.7%) Mizumoto et al, 2018;Seymour et al, 2018;Stoeckle et al, 2017) (Fig. 8, Table S2).…”
Section: Environmental Factors Effectsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 14, 2023. ; https://doi.org/10.1101/2023.06.13.544783 doi: bioRxiv preprint Goldberg et al, 2011); reptiles (Adams et al, 2019;Tarof et al, 2021); molluscs (Blackman et al, 2020;Goldberg et al, 2013;Ito and Shibaike, 2021;Mauvisseau et al, 2017;Miralles et al, 2019;Xia et al, 2018b) or crustaceans (Baudry et al, 2021;Harper et al, 2018a); but with no correlations being also found in some other studies, e.g., reptiles (Raemy and Ursenbacher, 2018) and crustaceans ; iii) organism size and developmental stage, with fish eDNA release rates being found to be higher in adults than in juveniles (Maruyama et al, 2014;Mizumoto et al, 2018), but no effect was found when eDNA concentration is adjusted taking into account total biomass (Mizumoto et al, 2018). For crustaceans, the presence of eggs increased eDNA concentrations per unit of mass (Crane et al, 2021;Dunn et al, 2017).…”
Section: Environmental Factors Effectsmentioning
confidence: 99%
“…It was then found in eastern Japan, including the Tokai and Kanto regions and the Yahagi River system in the 2000s and 2004, respectively (Ito 2015). One year later, the invasion of L. fortunei was reported in the Kabura-Gawa irrigation canal leading from the Ohshio Reservoir, and in Lake Kasumigaura (Sunoh 2006;Ito 2007Ito , 2015Ito & Shibaike 2021). In 2007, L. fortunei was found in the Tone River up to about 120 km from the estuary (Ito 2012).…”
Section: Occurrence Of L Fortunei In Japanmentioning
confidence: 99%
“…Although environmental DNA (eDNA) analysis is effective for early detection of invasive alien species (e.g. Ito & Shibaike 2021, Ficetola et al 2008, there appear to be two issues regarding eDNA de-tection in C. fluminea. First, there are no PCR primers that can detect only C. fluminea and distinguish it from C. sandai and C. japonica, which are native to Japan.…”
Section: Introductionmentioning
confidence: 99%